2023
DOI: 10.3390/microorganisms11020527
|View full text |Cite
|
Sign up to set email alerts
|

Partial Substitution of Urea with Biochar Induced Improvements in Soil Enzymes Activity, Ammonia-Nitrite Oxidizers, and Nitrogen Uptake in the Double-Cropping Rice System

Abstract: Biochar is an important soil amendment that can enhance the biological properties of soil, as well as nitrogen (N) uptake and utilization in N-fertilized crops. However, few studies have characterized the effects of urea and biochar application on soil biochemical traits and its effect on paddy rice. Therefore, a field trial was conducted in the early and late seasons of 2020 in a randomized complete block design with two N levels (135 and 180 kg ha−1) and four levels of biochar (0, 10, 20, and 30 t ha−1). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…The main causes of the decrease in carotenoid and chlorophyll synthesis under drought stress have been attributed to the decrease in the efficiency of carbon use and the increase in ethanol and lactate production (Ahanger et al, 2021). Our findings are similar to those of Ullah et al (2023) who reported that by reducing nitrogen loss and increasing nitrogen absorption, biochar enhances the concentration of photosynthetic pigments. Drought stress decreased the amount of nitrogen in aerial parts (data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…The main causes of the decrease in carotenoid and chlorophyll synthesis under drought stress have been attributed to the decrease in the efficiency of carbon use and the increase in ethanol and lactate production (Ahanger et al, 2021). Our findings are similar to those of Ullah et al (2023) who reported that by reducing nitrogen loss and increasing nitrogen absorption, biochar enhances the concentration of photosynthetic pigments. Drought stress decreased the amount of nitrogen in aerial parts (data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…These findings imply that, in the specific setting of this investigation, decreasing the usage of chemical fertilizers and incorporating biochar can form a promising strategy to improve fertilizer utilization efficiency. Studies have shown that biochar utilization increases the soil C/N ratio and limits nitrogen conversion and denitrification by soil microorganisms, which facilitates the sequestration of more NH 4 + and NO 3 − in the soil [33,59,60]. In addition, biochar can be used as an alternative to traditional phosphorus fertilizers because of its inherently high content of effective phosphorus, and it can impact and alter the cycling and effectiveness of phosphorus in soils through the adsorption and desorption of phosphorus and the regulation of the soil microbial community structure [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the application of biochar and vermicompost alone or in combination not only significantly increased the accumulation of NPK ( Figure 3 ) but also significantly improved the fertilizer utilization efficiency ( Table 3 ). Studies have shown that biochar application increases the soil C/N ratio and limits nitrogen conversion and denitrification by soil microorganisms, facilitating the sequestration of NH 4 + and NO 3 - in the soil ( Zhao et al., 2022 ; Ullah et al., 2023 ). In addition, biochar can be used as an alternative to traditional phosphorus fertilizers because of its inherently high effective phosphorus content, which can also alter the cycling and effectiveness of phosphorus in soils through the adsorption and desorption of phosphorus and regulation of the soil microbial community structure ( Kong et al., 2023 ; Pokharel and Chang, 2023 ; Yan et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%